Honestly Elliott - McDunn, Gillian (New York : Bloomsbury Children's Books, 2022)
Elliott is not quite sure where he fits in, but when he's paired with the super-popular Maribel for a school-wide contest, they both learn what it means to be a good friend and how to be the person others can count on.
3-6.
4.3.
Keywords: Friendship -- Juvenile fiction; Middle school students -- Juvenile fiction; Attention-deficit hyperactivity disorder -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Divorce -- Juvenile fiction; Children of divorced parents -- Juvenile fiction; Cooking -- Juvenile fiction; Friendship -- Fiction; Middle school students -- Fiction; Attention-deficit hyperactivity disorder -- Fiction; Fathers and sons -- Fiction; Divorce -- Fiction; Children of divorced parents -- Fiction; Cooking -- Fiction; School fiction